Assessing the impact of sample size and geology on earthen embankment design and construction - Ulloa, H. Omar; Ramirez, Alex; Jafari, Navid H.; Harrouch, Ignacio; Barth, Bradley (Frontiers in Built Environment, 2024)
This technical paper investigates the influence of sample size and geologic characteristics on the geotechnical design of levee embankments. Sample quality plays a vital role in quantifying engineering properties for levee embankment projects, and numerous studies have highlighted the impact of sample disturbance on such engineering properties. Despite this evidence, conventional tube and piston samplers of different diameters continue to be widely used, potentially leading to underestimation of shear strength. The paper focuses on comparing 7.6 cm and 12.7 cm diameter undisturbed Shelby tube samples and CPT data collected from three levee sites in the Greater New Orleans Area, Louisiana, USA, which encompass diverse geologic histories. The study aims to assess the effect of industry used samples size and geology on levee construction costs. The findings provide valuable insights into optimizing sample collection methods and improving geotechnical design for earthen embankments.